Early lumping observer design and sensor placement for transport-reaction systems. (April 2022) - Tello, Ivan F.Y.; Vande Wouwer, Alain; Coutinho, Daniel
Abstract: This paper deals with the observer design problem for a class of one-dimensional multi-species transport-reaction systems satisfying sector bounded nonlinearities and considering measurements distributed over the spatial domain. A design method is proposed based on a reduced-order model and a Lyapunov function, which provides sufficient conditions in terms of standard linear matrix inequalities (LMIs) to ensure the exponential convergence of the estimation error with a prescribed decay rate. The observer performance is further improved through an offline optimal sensor placement algorithm considering a parameterized reduced-order output matrix. A nonisothermal tubular reactor is presented to demonstrate the observer performance as well as the advantages of the proposed sensor placement optimization scheme. Highlights: An early-lumping observer is proposed for multi-species transport-reaction problems. Various sensor configurations are considered in the spatial domain. An optimal sensor placement algorithm is developed. The observer design is based on a Lyapunov function and linear matrix inequalities. A tubular reactor problem illustrates the good performance.